Thoughts on Refereed Articles. - Buffy Choinski (Issues in Science and Technology Librarianship, 2011)
The author discusses her views on refereed articles. She has been the Refereed Articles Editor for "Issues in Science and Technology Librarianship" since the journal started a refereed section in 2000. She discusses the common problems encountered by referees and editors. Some suggestions for referees and authors are presented.